Pengaruh Peristiwa Black October 2008 di Pasar Modal Amerika Serikat Terhadap Return Saham-Saham LQ45 di Pasar Modal Indonesia - , Himawan Yogieswara ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research is to study the events and analyze the impact of international events on the performance of stock markets in Indonesia. To prove integration of capital market and the influence of international events required Johansen cointegration test technique and Vector Error Correction Model (VECM) to see how the a stock market affects the stock market each other. The events in this study (event study) were Black October 2008, which occurred in the United States, while the capital market in Indonesia was represented by 60 stocks that have entered the category LQ 45 and actively traded in the duration 2003-2008. Periods of research conducted during the 121 days, 100 days estimation period and 21 period window. Date of event is determined on October 6, 2008 (the day of stock trading in Indonesia) or September 29, 2008 (when the stock trades in the United States) at the time the U.S. Congress decided to reject the bailout plan proposed by the government of George W. Bush to save the U.S. economy. United States Congress refusal is information that will be published, so the tests are carried out from development study to calculate the abnormal return, which occurs during the event. Assumption United States regional Composite Indexes are cointegrated with Indonesia Composite Index, so that the events of Black October 2008 in the United States has made stock prices on the stock exchange of the LQ 45 Indonesia generate negative abnormal returns because of that event classified as negative signal. Indonesian market quickly react for rapid information so it can be said that the Indonesian capital market is semi-strong efficient.